Current management of congenital anterior cranial base encephaloceles. (April 2020) - Thompson, Harrison M.; Schlosser, Rodney J.; McCarty Walsh, Erika; Cho, Do-Yeon; Grayson, Jessica W.; Karnezis, Thomas T.; Miller, Peter L.; Woodworth, Bradford A.
Abstract: Objectives: Congenital encephaloceles provide unique diagnostic and reconstructive challenges for the pediatric rhinologist. The objectives of the current study were to evaluate contemporary treatment strategies for congenital encephaloceles focusing on presentation, surgical technique, and outcomes. Methods: Multi-institutional retrospective chart review of congenital encephaloceles (2003–2019). Data regarding demographics, presenting symptoms, associated abnormalities, surgical technique, size, location, and complications were collected. Results: Fourteen patients with 15 congenital encephaloceles were treated using endoscopic techniques (avg 6.0 years, range 2 months–22 years) with mean follow up of 23 months. The majority presented with nasal obstruction (n = 13); only one child had cerebrospinal fluid (CSF) rhinorrhea. Associated anomalies included nasal deformities, congenital hypopituitarism, and Morning Glory syndrome. Average encephalocele size was 2.44 cm (range 0.5–3.6 cm) with mean skull base defect size of 8.6 x 7.7 mm. Locations included the foramen cecum (n = 9), central sphenoid (n = 3), midline anterior cranial fossa (n = 1), orbital plate of frontal bone (n = 1), and ethmoid roof (n = 1). Because of favorable expansion from encephaloceles, it was unnecessary to postpone surgeries to allow nasal cavity growth. Three individuals had prior operations, including surgeries for "nasal polyp" or "adenoid cyst". Two patients had post-operative complications (meningitis and CSF leak) effectively treated with no further sequelae. Conclusions: In the current study, congenital encephaloceles in children as young as 2 months were successfully repaired using endoscopic techniques. Endoscopic approaches remain a safe and effective intervention for management of these lesions.